2012
DOI: 10.1098/rspb.2012.1437
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing past species assemblages reveals the changing patterns and drivers of extinction through time

Abstract: Predicting future species extinctions from patterns of past extinctions or current threat status relies on the assumption that the taxonomic and biological selectivity of extinction is consistent through time. If the driving forces of extinction change through time, this assumption may be unrealistic. Testing the consistency of extinction patterns between the past and the present has been difficult, because the phylogenetically explicit methods used to model present-day extinction risk typically cannot be appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…Temporal changes in threats may shift the traits underlying extinction risk (Bromham et al. ; Lyons et al. ), but many of these traits appear general enough to create consistent long‐term differences in extinction risk (Harnik et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal changes in threats may shift the traits underlying extinction risk (Bromham et al. ; Lyons et al. ), but many of these traits appear general enough to create consistent long‐term differences in extinction risk (Harnik et al.…”
Section: Introductionmentioning
confidence: 99%
“…If these traits drive both ancient and modern extinctions, and tend to be conserved within lineages over time, then we may expect that extant clades with high contemporary extinction risk should also have high extinction rates over their history. Temporal changes in threats may shift the traits underlying extinction risk (Bromham et al 2012;Lyons et al 2016), but many of these traits appear general enough to create consistent long-term differences in extinction risk (Harnik et al 2012b;Finnegan et al 2015;Orzechowski et al 2015;Smits 2015). Though this concept has yet to be thoroughly tested, emerging evidence suggests that lineages suffering high contemporary extinction risk similarly had high rates of extinction in the fossil record (McKinney 1997;Condamine et al 2013;Finnegan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using IUCN threat status across taxonomic groups, some authors have found evidence for nonrandom extinction processes in angiosperm, avian, and mammalian phylogenies worldwide (Purvis et al, 2000;Vamosi & Wilson, 2008;Bromham et al, 2012), and in angiosperm phylogeny in Australia (Sjostrom & Gross, 2006). Using IUCN threat status across taxonomic groups, some authors have found evidence for nonrandom extinction processes in angiosperm, avian, and mammalian phylogenies worldwide (Purvis et al, 2000;Vamosi & Wilson, 2008;Bromham et al, 2012), and in angiosperm phylogeny in Australia (Sjostrom & Gross, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Given that extinction selectivities can vary with extinction agents (Chiba and Roy ; Bromham et al. ), knowledge of how PD is affected by individual threats should be a useful conservation tool – threats that are likely to result in large losses of PD are arguably more detrimental from an evolutionary standpoint compared with those with more limited impacts on PD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, existing estimates of future changes in PD tend to be largely based on aggregate losses of species on various Red List categories rather than extinctions due to specific threats (Purvis et al 2000;von Euler 2001;Mooers and Atkins 2003). Given that extinction selectivities can vary with extinction agents (Chiba and Roy 2011;Bromham et al 2012), knowledge of how PD is affected by individual threats should be a useful conservation toolthreats that are likely to result in large losses of PD are arguably more detrimental from an evolutionary standpoint compared with those with more limited impacts on PD.…”
Section: Introductionmentioning
confidence: 99%